Symposium dedicated to the 80th birth anniversary of Academician Arvo Krikmann at the Estonian Literay Museum - Liisa Granbom-Herranen (ELM Scholarly Press, 2022)
In July 2019, the renowned folklorist, academician Arvo Krikmann (1939–2017), would have turned 80. To celebrate this as well as to honour him and acknowledge the donation of Krikmann’s library to the Estonian Literary Museum, a symposium was organized at the Estonian Literary Museum on Saturday, September 7, under the auspices of the annual conference of the Centre of Excellence in Estonian Studies.